Implementation of particle swarm optimization for tuning of PID controller in Arduino Nano for solar MPPT system / Muhammad Iqbal Mohd Zakki, Mohd Najib Mohd Hussain and Nawawi Seroji - Mohd Zakki, Muhammad Iqbal; Mohd Hussain, Mohd Najib; Seroji, Nawawi (UiTM Press, 2018)
This paper presents the implementation particle swarm optimization (PSO) embedded in Arduino Nano for proportional-integral-derivative controller (PID) tuning as a validation for real-time hardware application on the photovoltaic maximum power point tracking (MPPT) system. The Arduino is interfaced to the MATLAB/Simulink via serial communication device to provide duplex communication for PID tuning. The performance of PID tuning using PSO in Arduino was compared with the performance of MATLAB PID tuner toolbox based on simulation result via Simulink. The embedded PSO-PID provides better performance of 10 times higher compared to MATLAB PID tuner.